2019
DOI: 10.1209/0295-5075/126/58001
|View full text |Cite
|
Sign up to set email alerts
|

Roles of mutation rate and co-existence of multiple strategy updating rules in evolutionary prisoner's dilemma games

Abstract: The emergence and maintenance of cooperation has attracted intensive scholarly interest and has been analysed within the framework of evolutionary game theory. The role of innovation, which introduces novel strategies into the population, is a relatively understudied aspect of evolutionary game theory. Here, we investigate the effects of two sources of innovation-mutation and heterogeneous updating rules. These mechanisms allow agents to adopt strategies that do not rely on the imitation of other individuals. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Before we proceed, we should note that the men-tioned non-transitive relation between competing partners may emerge in other types of evolutionary game models, too [24,25,26,27,28,29,30,31,32]. For instance, by introducing voluntary participation into the classic public goods game we can observe an RSP -type cycle among cooperators, defectors, and loners [33].…”
Section: Introductionmentioning
confidence: 99%
“…Before we proceed, we should note that the men-tioned non-transitive relation between competing partners may emerge in other types of evolutionary game models, too [24,25,26,27,28,29,30,31,32]. For instance, by introducing voluntary participation into the classic public goods game we can observe an RSP -type cycle among cooperators, defectors, and loners [33].…”
Section: Introductionmentioning
confidence: 99%
“…Here we consider the usual imitative rule [51], the Ising (or Glauber dynamics) rule [68], and the dynamic win-stay-loseshift (WSLS) rule [69]. This is done so we can study the robustness of the effects created by payoff perturbation, since previous works have extensively shown how the update rules can lead to different behaviors [22,34,35,47,70,71].…”
Section: Modelmentioning
confidence: 99%
“…In EGT, heterogeneity can be related to different aspects of a game, e.g., incentives, interaction topology, learning rates, and dynamics. Previous investigations, such as [22,29,[33][34][35][36][37][38], showed that heterogeneity can support cooperative behaviors in many competitive scenarios. At the same time, other studies such as [39] reported that heterogeneous networks do not promote cooperation when humans play the prisoner's dilemma.…”
Section: Introductionmentioning
confidence: 99%
“…Individual migration is an essential characteristic of living organisms [22]. It has been demonstrated that the mode of individual mobility does influence the evolutionary dynamics of cooperation among unrelated individuals, which has attracted intensive research activity in recent years [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Theoretical and experimental studies have shown that individual mobility can promote the evolution of cooperation [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%